Above the Matrix: Functional Roles for Apically Localized Integrins - Peterson, Raven J.; Koval, Michael (Frontiers in Cell and Developmental Biology, 2021)
Integrins are transmembrane proteins that are most typically thought of as integrating adhesion to the extracellular matrix with intracellular signaling and cell regulation. Traditionally, integrins are found at basolateral and lateral cell surfaces where they facilitate binding to the ECM and intercellular adhesion through cytosolic binding partners that regulate organization of actin microfilaments. However, evidence is accumulating that integrins also are apically localized, either endogenously or due to an exogenous stimulus. Apically localized integrins have been shown to regulate several processes by interacting with proteins such as connexins, tight junction proteins, and polarity complex proteins. Integrins can also act as receptors to mediate endocytosis. Here we review these newly appreciated roles for integrins localized to the apical cell surface.